2019
DOI: 10.21320/2500-2139-2019-12-2-173-178
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of PRAME Activity in Tumor Cells of Follicular Lymphoma

Abstract: Цель. Определить параметры выживаемости больных фолликулярной лимфомой (ФЛ) в группах с различным уровнем экспрессии гена PRAME в опухолевых клетках. Материалы и методы. В работе собраны образцы лимфатических узлов, крови и аспирата костного мозга 34 первичных больных ФЛ. Уровень экспрессии гена PRAME в опухолевых клетках (центроцитах и центробластах) оценивался методом количественной ПЦР в реальном времени. Изучалось влияние разного уровня экспрессии PRAME на параметры выживаемости больных с медианой наблюден… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Another study showed that a high PRAME expression level in follicular lymphoma patients had a negative prognostic value only in the presence of parameters determining high FLIPI-1 and FLIPI-2 risk. PRAME expression level and FLIPI-1/FLIPI-2 values together enabled the most reliable prediction of early mortality in follicular lymphoma patients [109].…”
Section: Prame As a Biomarkermentioning
confidence: 98%
“…Another study showed that a high PRAME expression level in follicular lymphoma patients had a negative prognostic value only in the presence of parameters determining high FLIPI-1 and FLIPI-2 risk. PRAME expression level and FLIPI-1/FLIPI-2 values together enabled the most reliable prediction of early mortality in follicular lymphoma patients [109].…”
Section: Prame As a Biomarkermentioning
confidence: 98%
“…In our previous works, we showed the possibility of using fluorescent antibodies to the PRAME protein obtained by oxime ligation as a molecular diagnostic tool [ 31 , 34 , 35 ]. We demonstrated that fluorescent anti-PRAME antibodies allow for immunotyping bone marrow cells of patients with acute leukemia for the presence of the PRAME protein [ 31 ], which significantly affects the course of the disease and further prognosis [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%